Modification Of Starch Using Cross-Linking Method On The Physical And Chemical Properties Of Yam (Dioscorea alata) - Widia Lesmana Ritonga; Budi Suarti (Universitas Muhammadiyah Palembang, 2024)
Natural starch from the uwi (Dioscorea alata) plant is used extensively as a thickening, film-forming agent, and food ingredient in the food industry. Natural starch derived from a variety of plants often has certain characteristics that limit its use in certain culinary items. Modifying starch is one way to enhance its physical and chemical qualities, among other approaches. Adding STPP was the chemical alteration procedure used in this investigation. Sodium tripolyphosphate, or STPP, is a preservative and texture enhancer that is often used in food. By raising the gelatinization temperature, strengthening chemical bonds, avoiding retrogradation, and making the starch resistant to low pH and stirring operations, this replacement aims to increase the starch's durability. The study was placed at Muhammadiyah University of North Sumatra's Faculty of Agriculture's Agricultural Product Technology Laboratory. The research was conducted using a two-replicat Factorial Randomized Complete Block Design (RCBD). Consideration of STPP, abbreviated as S, is the first component. There are four possible values ​​for S: 0%, 2%, 4%, and 6%. Second, there are four degrees of stirring time, represented as (P): 35 minutes, 45 minutes, 55 minutes, and 65 minutes. Protein, frozen liquid, color (L, a, b*), and water absorption capability were among the metrics that were noted. Protein and color values ​​(L*, a*, b*) were found to increase with the addition of sodium tripolyphosphate in all treatments, but water absorption capacity and frozen liquid stability were found to decrease. While color metrics (a*, b*) rose across all treatments, protein, water absorption capacity, frozen liquid stability, and color (L*) all decreased as a result of stirring time. The findings show that each treatment was affected by the percentage of sodium tripolyphosphate and the amount of time it took to stir. The S1 treatment, which included 2% STPP, and the P2 treatment, which had 45 minutes of stirring, yielded the best outcomes. This study suggests that more STPPs be included in future studies to see whether better outcomes are possible.